Reflections on The Image of Green Buildings: An Ethnographic Evaluation of A “LEED” Certified Elementary School - Mansour, Osama E. (Proceedings of the Annual Architectural Research Symposium in Finland, 2014)
Davidson Elementary School is the first LEED certified school building in Tucson, Arizona, the school has been designed and built as a green setting based on the goals of the architect, teachers, parents and a community that has long suffered from the moldy old Davidson school building. Yet by looking at the new building and comparing it with conventional schools with similar function and size in Tucson, Arizona, one questions whether the users can distinguish differences which might be related to the building’s greenness? Is the same true for many other LEED rated green school buildings in other parts of United States? The present paper asks whether the image of a building, and even an integrated pedagogy in the case of schools, shouldn’t more actively promote the meaning of sustainability. The present case is an ethnographic study has been done at Davidson Elementary School during the author’s sabbatical at University of Arizona in 2010. The study included analysis for the images of the building as well as interviews with the principal, teachers, administrative staff, 4th and 5th grade students and parents. The ethnographic evaluation shows that Davidson Elementary Buildings offers limited use of symbolic meanings to foster belief about sustainability; at the same time it conveys some negative meanings to laypeople, obviously hindering a possible sustainable relationship between people and environment. The examination of the cultural expression of buildings’ green features and the meanings acquired from them at Davidson School provides a novel ethnographic evaluation of green building design intentions.